2009
DOI: 10.1039/b805160g
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the matrix effects on a HPLC-ESI-MS/MS method and application for monitoring triazine, phenylurea and chloroacetanilide concentrations in fresh and estuarine waters

Abstract: In this work, the effects of matrix interferences on the analytical performance of a new multiresidue method based on off-line solid phase extraction followed by reversed-phase liquid chromatographic separation and electrospray triple quadrupole mass spectrometric detection were investigated. This technique allows the simultaneous determination of 30 triazines, phenylureas and chloroacetanilides, extracted from freshwaters, in 40 minutes. Quantifications were performed with the use of appropriate internal stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The impact of matrix effects on the ESI signal has been previously investigated [26,27]. A signal enhancement of around 10 % was observed for BMAA derivatized with AQC [28].…”
Section: Resultsmentioning
confidence: 93%
“…The impact of matrix effects on the ESI signal has been previously investigated [26,27]. A signal enhancement of around 10 % was observed for BMAA derivatized with AQC [28].…”
Section: Resultsmentioning
confidence: 93%
“…Among several ionization modes, ESI has been proven to be reliable, robust, and sensitive [13][14][15]. Nevertheless, even if HPLC-ESI-MS/MS is used for quantitative purposes, it can also be hampered by the presence of co-eluting matrix compounds, such as humic acids that might interfere with the ionization of the target analyte and its quantitation [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography coupled to mass spectrometry has been widely employed (Sanchez-Ortega et al 2009;Bagheri et al 2010;Djozan et al 2010;Katsumata et al 2010;Matamoros et al 2010;Navarro et al 2010;Portoles et al 2011;Bagheri et al 2012), and the use of liquid chromatography with different detectors such as ultraviolet (Hu et al 2009a, b;Zhou et al 2009;Beale et al 2010;See et al 2010), diode array (Kueseng et al 2009;Wang et al 2010Wang et al , 2011Rodríguez-González et al 2013) or mass spectrometry (Mazzella et al 2009;van Pinxteren et al 2009;Dujakovic et al 2010;García-Galán et al 2010;Postigo et al 2010;Trtic-Petrovic et al 2010;Lissalde et al 2011) was also reported.…”
Section: Introductionmentioning
confidence: 93%